2022
DOI: 10.1093/cid/ciac450
|View full text |Cite
|
Sign up to set email alerts
|

Testing Frequency Matters: An Evaluation of the Diagnostic Performance of a Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Rapid Antigen Test in US Correctional Facilities

Abstract: Background The CDC recommends serial rapid antigen assay collection within congregate facilities. Though modeling and observational studies from communities and long-term care facilities have shown serial collection provides adequate sensitivity and specificity, the accuracy within correctional facilities remains unknown. Methods Using Connecticut Department of Corrections (DOC) data from November 21st 2020 to June 15th 2021,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…Our effect estimates on infectiousness during the Omicron period, while imprecise, are in alignment with a prior study by Tan et al 41 This study, conducted in California correctional facilities, found that the prior infection and vaccination status of an index case reduced the risk of transmission by 40% (20-55%) and 22% (6-36%), respectively. Similarly, we found that the risk of transmission following a cell exposure was 0.72 (0.25-2.03) times lower among infected residents with a prior infection and 0.52 (0.2-1.36) times lower among infected residents with a history of vaccination than residents without a prior infection or history of vaccination.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our effect estimates on infectiousness during the Omicron period, while imprecise, are in alignment with a prior study by Tan et al 41 This study, conducted in California correctional facilities, found that the prior infection and vaccination status of an index case reduced the risk of transmission by 40% (20-55%) and 22% (6-36%), respectively. Similarly, we found that the risk of transmission following a cell exposure was 0.72 (0.25-2.03) times lower among infected residents with a prior infection and 0.52 (0.2-1.36) times lower among infected residents with a history of vaccination than residents without a prior infection or history of vaccination.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, we found that the risk of transmission following a cell exposure was 0.72 (0.25-2.03) times lower among infected residents with a prior infection and 0.52 (0.2-1.36) times lower among infected residents with a history of vaccination than residents without a prior infection or history of vaccination. Though our precision prevents us from making broad conclusions from these findings, they support the findings of Tan et al 41…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In correctional facilities, Lind et al [30] showed that serial RAgTs had higher but diminishingly improved sensitivities over time, similar to the diminishing returns seen with repeat testing in the collaborative study. In a university setting, Smith et al [31] found that serial testing multiple times per week increased the sensitivity of RAgTs.…”
Section: Discussionmentioning
confidence: 68%
“…Some COVID-19 patients with low viral loads in the early disease stage may be missed by the RAgT assay. Through serial specimen collection, the three-rapid antigen test can increase the sensitivity of RAgT from 68.5% to an enough high level of 95.8% ( 13 ). The very high NPV suggests that individuals with negative RAgT results are temporarily not infectious, and whether the nucleic acid based-test is positive or negative, these recovered COVID-19 patients should be allowed to stop isolation immediately.…”
Section: Discussionmentioning
confidence: 99%